Dynamics of formation of soliton conductivity in a 2D-array of linear chains containing commensurate charge density wave near the contact with a normal metal - Pershin, Yurij V.; Rozhavsky, Alexander S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
We make a numerical study of the conversion of conduction electrons into charge density wave (CDW) topological solitons at the interface between a normal metal and a 2D-array of the CDW-carrying linear chains. The interplay of commensurability potential, interchain interaction, and electric field on the dynamics of soliton formation is studied. When the interchain interaction exceeds the commensurability energy, the dynamic mechanism of creation of fractionally charged solitons near the contact is suppressed and specific contact nonlinearity in transport current is not observed.